Towards a scalable bioprocess for rAAV production using a HeLa stable cell line - Escandell, José (2023)
Funding Information: We thank Dr. Maria João Sebastião, Dr. Mafalda Dias, Maria Gonçalves and Mariana Antunes for their helpful discussion and experimental support. This work was funded by Fundação para a Ciência e Tecnologia/Ministério da Ciência, Tecnologia e Ensino Superior (FCT/MCTES, Portugal) through national funds to iNOVA4Health (UIDB/04462/2020 and UIDP/04462/2020), the Associate Laboratory LS4FUTURE (LA/P/0087/2020) and project PTDC/BTM-ORG/1383/2020, and by the European Union's Horizon 2020 research and innovation programme under the Marie Sklodowska-Curie grant agreement No. 813453 and TRANSVAC2 No. 730964; J.M.E. is funded by Stimulus of Scientific Employment, Individual Support program (2020.01216.CEECIND) from FCT; F.M is funded by PhD fellowship (2022.11494.BD) from FCT. Images were generated with Biorender.com. Funding Information: We thank Dr. Maria João Sebastião, Dr. Mafalda Dias, Maria Gonçalves and Mariana Antunes for their helpful discussion and experimental support. This work was funded by Fundação para a Ciência e Tecnologia/Ministério da Ciência, Tecnologia e Ensino Superior (FCT/MCTES, Portugal) through national funds to iNOVA4Health (UIDB/04462/2020 and UIDP/04462/2020), the Associate Laboratory LS4FUTURE (LA/P/0087/2020) and project PTDC/BTM‐ORG/1383/2020, and by the European Union's Horizon 2020 research and innovation programme under the Marie Sklodowska‐Curie grant agreement No. 813453 and TRANSVAC2 No. 813453; J.M.E. is funded by Stimulus of Scientific Employment, Individual Support program (2020.01216.CEECIND) from FCT; F.M is funded by PhD fellowship (2022.11494.BD) from FCT. Images were generated with Biorender.com . Publisher Copyright: © 2023 The Authors. Biotechnology and Bioengineering published by Wiley Periodicals LLC.